(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article discusses the pedagogical and psychological methods of introducing preschool children to folk tales as an essential component of early childhood education. Folk tales serve as a rich source of linguistic, moral, and imaginative development, offering children opportunities to explore universal human values and emotional experiences through narrative form. The study highlights effective strategies such as dramatization, visual storytelling, dialogic reading, and art-based activities that facilitate children’s comprehension and emotional engagement.